The human amygdala is sensitive to the valence of pictures and sounds irrespective of arousal: an fMRI study. - Anders, S; Eippert, F; Weiskopf, N; Veit, R (2008)
With the advent of studies showing that amygdala responses are not limited to fear-related or highly unpleasant stimuli, studies began to focus on stimulus valence and stimulus-related arousal as predictors of amygdala activity. Recent studies in the chemosensory domain found amygdala activity to increase with the intensity of negative and positive chemosensory stimuli. This has led to the proposal that amygdala activity might be an indicator of emotional arousal, at least in the chemosensory domain. The present study investigated amygdala activity in response to visual and auditory stimuli. By selecting stimuli based on individual valence and arousal ratings, we were able to dissociate stimulus valence and stimulus-related arousal, both on the verbal and the peripheral physiological level. We found that the amygdala was sensitive to stimulus valence even when arousal was controlled for, and that increased amygdala activity was better explained by valence than by arousal. The proposed difference in the relation between amygdala activity and stimulus-related arousal between the chemosensory and the audiovisual domain is discussed in terms of the amygdala's embedding within these sensory systems and the processes by which emotional meaning is derived.